Effect of irrigation frequency on growth and production of a cucumber crop under soilless culture - Nikolaou, Georgios; Neocleous, Damianos; Katsoulas, Nikolaos; Kittas, Constantinos (Emirates Journal of Food and Agriculture, 2017)
Three irrigation frequencies were applied on a soilless cucumber crop, in a greenhouse located in the coastal area of southern Cyprus. Irrigation scheduling was based on solar radiation and performed whenever accumulated solar radiation energy outside the greenhouse reached 1.3 MJ m-2 [High Irrigation Frequency (HIF)], 1.9 MJ m-2 [Medium Irrigation Frequency (MIF)] and 3.0 MJ m-2 [Low Irrigation Frequency (LIF)]. The amount of water applied was 0.192 Kg m-2, 0.288 Kg m-2 and 0.448 Kg m-2 for high, medium and low irrigation frequencies, respectively. Appropriately, the total volume of water applied was identical in each of the three cases. In order to study the effects of irrigation frequency on cucumber crops, multiple measurements were taken; the fresh and dry weight of plant organs (i.e. leaves, stem and fruit), marketable fresh yield production, and microclimate variables for a 75 day period, beginning in April and ending in June. The results revealed that the irrigation frequency did not influence the cucumber crop’s growth and production. Plants at LIF were facing water stress conditions, as estimated from leaf temperature and stem micro variation measurements. However, HIF increased the transpiration rate of the plants, resulting in less water and nutrient losses.